Going Public and Listing of Life Insurance Companies on Stock Markets and Profit Sharing in Korea: A Legal Study - Park, Semin (Columbia Journal of Asian Law, 2000)
Throughout the 1990’s, the Korean economy has experienced full- swing deregulation, market opening, and globalization. Life insurance companies in Korea have been struggling for survival in this era of unlimited competition; in the wake of the financial crisis that hit the nation at the end of 1997, these companies have witnessed the fall of several uncompetitive rivals during the government-led restructuring of the nation’s major industries. Recently, the listing of life insurance companies on the Korean stock market has become the center of the debates across the nation. This debate started when Lee Kun-hee, the Chairman of the Samsung Group, offered to sell 4 million shares of Samsung Life Insurance Company in an effort to bear a part of the enormous debt owed by the startup Samsung Motors, one of its affiliated companies. Lee was under pressure to hold him responsible for the debt due to Samsung Group’s glaringly inefficient investment in Samsung Motors. During the period of IMF control of the Korean economic system, Samsung and Daewoo, two of the leading Korean conglomerates, had attempted a so-called “big-deal” swap of Samsung Motor Company and Daewoo Electronics as a part of the government-led restructuring of the nation’s chaebol (conglomerates), but had gotten nowhere. With his back to the wall, Lee decided to offer his own stock holdings for sale. This move began the debate over various points concerning the listing of Samsung Life Insurance as well as Kyobo Life insurance, which also expressed its intention to go public.